Pengaruh Pengembangan Karir, Kompetensi dan Gaya Kepemimpinan Terhadap Kepuasan Kerja dengan Mediasi Komitmen Organisasional (Studi Kasus Pada PT Primatexco Indonesia Batang) - Putranto Hari Widodo (Universitas Peradaban, 2017)
The purpose of this study was to examine and analyze the influence of career development, competence and leadership style on job satisfaction with the mediation of organizational commitment (a study on PT PRIMATEXCO INDONESIA BATANG). The number of sample number 170 people. Primary data obtained using a questionmaire developed by the indicator variable of career development, competency, leadership style, organizational commitment and job satisfaction. Value score questionnaire using Likert scale of 1 to 5 continum. Methods of data using multiple regression analisis. The results of hypothesis testing and career development competencies have a positive and significant impact on organizational commitment. Style of leadership does not have a positive and significant impact on organizational commitment. Career development, competency, leadership style and organizational commitment have a positive and significant impact on job satisfaction.